Hemoglobin variants detected by hemoglobin A1c (HbA1c) analysis and the effects on HbA1c measurements. - Nasir, N.M.; Thevarajah, M.; Yean, C.Y. (Medknow Publications, 2010)
Knowledge of hemoglobin variants affecting HbA1c measurements is essential, in order to avoid mismanagement of diabetic patients.